Risperidone and ritanserin but not haloperidol block effect of dizocilpine on the active allothetic place avoidance task - Valešová, Věra; Stuchlík, Aleš; Svoboda, Jan; Bureš, Jan; Valeš, Karel (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Spatial working memory or short-term place memory is impaired in schizophrenia. The efficiency of antipsychotic drugs, particularly of typical antipsychotics, on cognitive deficit in schizophrenia remains disputable. Inhibition of serotonin (5-HT) 2A/2C receptors is important for cognitive improvement in schizophrenic patients treated with antipsychotics. The aim of the present work was to establish the effect of the 5-HT2A/2C receptor antagonist ritanserin (2.5 or 5 mg/kg), the dopamine D2 antagonist haloperidol (0.1 or 1 mg/kg), and the atypical antipsychotic risperidone (0.1 mg/kg or 1 mg/kg), which is an antagonist of both 5-HT2A/2C and D2 receptors, on cognitive deficit induced by subchronic administration of dizocilpine (MK-801, 0.1 mg/kg). We used the active allothetic place avoidance (AAPA) task, requiring the rat to differentiate between relevant and irrelevant stimuli, in a way similar to disruption of information processing disturbed in schizophrenic patients. Our results show that treatment with 5-HT2A/2C receptor antagonists, regardless of their effect on D2 receptors, blocked the cognitive impairment produced by MK-801. Haloperidol did not sufficiently reduce the deficit in AAPA induced by MK-801. Interestingly, administration of risperidone and haloperidol alone, but not ritanserin, impaired the AAPA performance in intact rats. Ritanserin and risperidone actually improve cognition independently of their effect on locomotor activity in an animal model of schizophrenia-like behavior. This finding is in accordance with the assumption that some antipsychotics are primarily effective against cognitive dysfunction in schizophrenia.
Keywords: financování organizované; Animals; Dizocilpine Maleate; Rats, Wistar; Avoidance Learning; Time Factors; haloperidol; časové faktory; chování zvířat; Haloperidol; ritanserin; risperidon; Ritanserin; Risperidone; Financing, Organized; Male; dizocilpinmaleát; učení vyhýbat se; krysa rodu Rattus; Behavior, Animal; zvířata; mužské pohlaví; Rats; potkani Wistar